Silicon nitride surface chemistry: A potent regulator of mesenchymal progenitor cell activity in bone formation. (December 2017) - Pezzotti, Giuseppe; Bock, Ryan M.; Adachi, Tetsuya; Rondinella, Alfredo; Boschetto, Francesco; Zhu, Wenliang; Marin, Elia; McEntire, Bryan; Bal, B. Sonny; Mazda, Osam
Graphical abstract: Highlights: Heat-treated Si3 N4 substrates affected metabolic function of mesenchymal cells. N-apatite phase promoted protein adhesion, cells differentiation, bone formation. Crystallographic constraints and released nitrogen modulated cell functions. Abstract: Polycrystalline silicon nitride (Si3 N4 ), sintered with the addition of minor fractions of yttrium and aluminum oxides ( i.e., Y2 O3 and Al2 O3 ), possesses uniquely adjustable surface chemistry that results in improved cell metabolism and enhanced bone formation. Building upon previous in vitro mineralization studies using osteosarcoma cells, this study examined interactions between various chemically modulated Si3 N4 surfaces and murine mesenchymal progenitor cells (KUSA-A1). It was discovered that various pressurized thermal-treatments coupled with adiabatic and non-adiabatic cooling of sintered Si3 N4 samples resulted in partial or full coverage of their surfaces with different Si–Y–O–N compounds. Full coverage by mostly yttrium silicate (β-Y2 Si2 O7 ) was obtained by non-adiabatic cooling, whereas partial coverage with N-apatite (Y10 (SiO4 )6 N2 ) occurred under adiabatic conditions. These peculiar phases were found to be particularly efficient in stimulating the in vitro differentiation of KUSA-A1 cells into osteoblasts, although according to different microscopic mechanisms. The final amount of bone formation was nearly identical for both phases. Cell differentiation was monitored by assessing the concentration of the osteogenic marker γ-carboxyglutamate ( i.e., Gla-osteocalcin). It was found to be ∼45% higher for Si3 N4 samples possessing the N-apatite phase than for biomedical titanium alloy controls tested under exactly the same conditions. Concurrent measurements of the bone resorption marker Glu-osteocalcin ( i.e., an undercarboxylated form of γ-carboxyglutamate) showed significant inhibition of osteoclastogenesis on these surface-treated Si3 N4 samples as compared to the controls. Bone formation was assessed using in situ Raman microprobe spectroscopy and ex situ laser microscopy. These two independent analytical techniques consistently found an increase of ∼80% in expressed hydroxyapatite when compared to a biomedical titanium alloy. This study suggests that surface-treated Si3 N4 may have a powerful anabolic, differentiating, and antiapoptotic effect on osteoblasts in vitro, and a concurrent inhibitive action on osteoclastogenesis. Given additional research, Si3 N4 may represent a new therapeutic solution for bone disorders and for engineered implants that physiologically regulate bone growth processes.